Quantitative Proteomic Analysis of Germination of Nosema bombycis Spores under Extremely Alkaline Conditions - Liu, Han; Chen, Bosheng; Hu, Sirui; Liang, Xili; Lu, Xingmeng; Shao, Yongqi (Frontiers in Microbiology, 2016)
The microsporidian Nosema bombycis is an obligate intracellular pathogen of the silkworm Bombyx mori, causing the epidemic disease Pebrine and extensive economic losses in sericulture. Although N. bombycis forms spores with rigid spore walls that protect against various environmental pressures, ingested spores germinate immediately under the extremely alkaline host gut condition (Lepidoptera gut pH >10.5), which is a key developmental turning point from dormant state to infected state. However, to date this process remains poorly understood due to the complexity of the animal digestive tract and the lack of genetic tools for Microsporidia. Here we show, using an in vitro spore germination model, how the proteome of N. bombycis changes during germination, analyse specific metabolic pathways employed in detail, and validate key functional proteins in vivo in silkworms. By a label-free quantitative proteomics approach that is directly based on high-resolution mass spectrometry (MS) data, a total of 1136 proteins were identified with high conﬁdence, with 127 proteins being significantly changed in comparison to non-germinated spores. Among them, structural proteins including polar tube protein 1 and 3 and spore wall protein (SWP) 4 and 30 were found to be significantly down-regulated, but SWP9 significantly up-regulated. Some nucleases like polynucleotide kinase/phosphatase and flap endonucleases 1, together with a panel of hydrolases involved in protein degradation and RNA cleavage were overrepresented too upon germination, which implied that they might play important roles during spore germination. The differentially regulated trends of these genes were validated respectively by quantitative RT-PCR and 3 proteins of interest were confirmed by Western blotting analyses in vitro and in vivo. Furthermore the pathway analysis showed that abundant up- and down-regulations appear involved in the glycolysis, pentose phosphate pathway, purine and pyrimidine metabolism, suggesting preparations of energy generation and substance synthesis for the following invasion and proliferation inside the host. This report, to our knowledge, provides the first proteomic landscape of N. bombycis spores, and also a stepping stone on the way to further study of the unique infection mode of this economically important pathogen and other microsporidia in general.